A situated perspective on self-regulated learning from a person-by-context perspective. (3rd July 2019) - Ben-Eliyahu, Adar
ABSTRACT: The situated nature of self-regulated learning (SRL) was investigated across two studies with gifted students. In Study 1, profile-centered analyses of academic cognitive-behavioral SRL revealed three groups of gifted undergraduate students (N=149): high regulated, regulated, and behaviorally dysregulated. In comparing gifted group profiles with typically achieving students, findings suggest that typical students most resemble the regulated group. Overall, the behaviorally dysregulated group reported lower levels of social and academic SRL and achievement goal orientations from the high-regulated group. No differences were found in trait emotion regulation or self-control suggesting a situated effect of SRL. In Study 2 gifted (N=188) and typically achieving (N=83) undergraduate students reported on their SRL and motivation in their favorite and least favorite courses. Structural equation modelling analyses showed that, for gifted students, there were more relations between motivation and SRL than typical students. For example, mastery goal orientation predicted all forms of SRL for gifted students but not for typical students. This suggests that gifted students may be more calibrated and adept at drawing on motivation to shape SRL. Taken together, the findings from both studies show that gifted students are a heterogenous population, and that there are some similarities to typical students.